Kinerja UMKM Melalui Prespektif Entrepreneurial Marketing dan Kapabilitas Inovasi - Maimunah; Miftahul Jannah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study aims to determine the effect of Innovation Capability and Entrepreneurial Marketing on the Performance of MSMEs in Bangkalan district. This research is quantitative research with data collection through questionnaires to measure the number of respondents' responses. The data was analyzed by linear regression test. The sampling technique used purposive sampling technique. A total of 130 MSME respondents who have been running for at least 3 years were sampled. The results of this study indicate that the partial test of the entrepreneurial marketing variable states that it has no significant effect on the performance of MSMEs, while the innovation capability variable has a significant effect on the performance of MSMEs and entrepreneurial marketing simultaneously has a significant effect on the performance of MSMEs. However, this study has limitations in the form of the sample used is limited to the population of MSMEs in Bangkalan Regency. Therefore, it is recommended for future researchers to develop the breadth or depth of the research object so that the empirical results obtained can better reflect existing phenomena.